Annual reports : delivering your corporate message to stakeholders - Stittle, John (Gower, 2003)
This book concentrates on ensuring that the 'corporate message' is communicated to stakeholders in a way that maximises the value of the annual report and outlines how this might best be achieved. It explains the importance not only of the quantitative (a.